Weather Effect On Discoloration of Fiber Plastic Composite Made of Corrugated Paper and Polyethylene with The Addition Of Maleic Anhydride and Benzoyl Peroxide - Vicky Fadliansah Sihombing; Luthfi Hakim; Ridwanti Batubara (Program studi Kehutanan USU, 2014)
The use of fiberplastic composite (FPC) for exterior purposes raises issues related to durability FPC against weather influences. Discoloration is one problem that often occurs in the products that are used for the purpose of exterior use. Discoloration of the product exposed to weather effects will reduce the aesthetic appearance of a product.The main objective of this research was to evaluate discoloration of FPC after exposed to weather for 6 months.In this study, there were 6 treatments consisting of two factors, namely the ratio of FPC materials (corrugated paper fibers and polyethylene) which consists of 3 levels ie 50:50, 60:40 and 70:30 and the additional factor of maleic anhydride (MAH), which consists of two levels, namely 5% and 7%.The results showed that after exposure to the weather for 6 months, the discoloration on the FPC are initially black to white dull. At the70:30 ratio with the addition of 7% MAH the discoloration are not too drastic than in the comparison of 50:50 and 60:40. Discoloration on the surface of the FPC caused by photodegradation by UV light. Degradation mainly occurred in the lignin component and cause discoloration. The addition of MAH cannot reduce discoloration of the FPC after exposure for 6 months.Keywords : fiber plastic composite, discoloration, weathering test.